Analisis Kualitas Gizi MP-ASI Instan Berbasis Gembili dengan Fortifikasi Tepung Daun Kelor, Ikan Teri dan Telur Puyuh: Nutritional Quality of Gembili-Based Instant Complementary Food Fortified with Moringa Flour, Anchovy, and Quail Egg - Destiana Adinda Putri; Sri Winarti; Anna Abdilla; Aulia Islamiati Yusuf; Muhammad Rosyid Wardianto; Candra Ayu Devi Lukitasari (Jurnal Teknologi dan Mutu Pangan, 2026)
Stunting remains a chronic nutritional problem in Indonesia, highlighting the need to develop complementary foods (MP-ASI) based on local food resources. Gembili tubers are a potential source of carbohydrates and inulin, moringa leaves are rich in vitamins and minerals, and quail eggs provide a high-quality source of animal protein. This study aimed to develop and evaluate instant MP-ASI powder formulated from gembili flour enriched with moringa leaf flour and quail eggs, processed using the foam mat drying method. A factorial Completely Randomized Design was applied with two factors: moringa flour proportions (15%, 20%, 25%) and quail egg proportions (75%, 80%, 85%). Results showed significant effects (p≤0.05) and interactions between factors on moisture and carbohydrate levels. Moisture ranged from 2.18–6.56%, with the highest found in the 25% moringa and 85% quail egg combination. Protein content increased with both ingredients, and all formulations met national MP-ASI standards. Ash content decreased as moisture increased. Quail eggs significantly affected fat content, whereas moringa flour did not. Carbohydrates ranged from 59.72–71.92% and decreased as non-carbohydrate components increased. These findings suggest that this formulation has strong potential as a locally sourced complementary food to support stunting prevention.